Unveiling Political Persuasion: Speech Acts in the 2024 Indonesian Presidential Candidates' Speech Texts - Sosrohadi, Somadi; Syukri, Muhammad; Arismanto Sosrohadi, Andri (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This research aims to describe the forms of persuasion and types of political propaganda carried out by the three Candidates for President of the Republic of Indonesia in 2024. This type of research is a theoretical and methodological approach by analyzing words, phrases, clauses and sentences containing persuasive speech acts in the text speeches by three Indonesian Presidential Candidates in 2024. The sampling technique in this research was based on predetermined criteria. The results of this research obtained the use of imperative sentences by presidential candidates are more about requests, prohibitions and omissions. This shows that the presidential candidate is a speaker who positions himself lower than his speech partner (audience). For this reason, the Presidential Candidate in his speeches always asks and hopes for the people to be accepted and accepted in society. Meanwhile, the political propaganda carried out by the presidential candidates is based on the vision and mission in their speeches. They asked and expected the people to accept and follow what was in the contents of their speech. The presidential candidates' speeches are political propaganda speeches that can be combined with a vision and mission and then carried out persuasively.